Brand equity and packaging design impact on customer loyalty to kedai rakyat 1 Malaysia products - Zainal Abidin, Sazrinee (2019)
Quality deficiency of brand equity through packaging design that could impacts the customer loyalty towards Kedai Rakyat 1 Malaysia (KR1M) products in Malaysia. The purpose of this study is to investigate on how the brand equity would give an impact to the customer loyalty of KR1M products in Malaysia . The first stage of the study uses literature in investigating the key characteristics of branding towards packaging applications’ by adapting the branding theory. Then, it uses customer loyalty elements in strategising on how the product should attract consumer. Finally, it uses the packaging design applications in the current market to document and identified the packaging design applications’ trends that make the product successful in attracting the customer loyalty. This study was using the quantitative methods and later validated with several interviews with professional and expert in the branding and design fields. Sampling of 320 respondents were collected from 14 states all over Malaysia with a mixture of KR1M stores in urban and semi urban area. The raw data was processed using SPSS 24 and tested with method of correlations to further investigate the credibility of the data. Result of the study would increase the depth understanding towards the integration of branding and packaging design; and understanding the elements of products that could magnetise consumer. The result expected to lead towards identifying and adapting theory on integrated research within marketing, branding and design towards KR1M product; and interrelated theories will create significant theories to drive research output. After the introduction of the background problem, this study will present the literature review on brand equity, customer loyalty, packaging design and describe the research methodology before presenting the expected results. This study contributes in providing a clear guidelines and criteria to assist KR1M designer, manufacturer and retailers in increasing the customer loyalty. It is very significant to generate new knowledge that is beneficial towards quality which will lead towards better product integrity. The final stage of this study contributes the propose 'Standard Operating Procedure' in providing a packaging design criteria and branding processes that could contributed customer loyalty through branding and packaging design not only for KR1M product only. The SOP was validated by the professional that it could also be universally use for all types of packaging design.